THE RATIONAL SCHEME DEFINITION OF THE CROSSTRUSSWEB ALONG THE BOTTOM CHORD OF INDUSTRIAL BUILDINGTRUSSES (Collection of scientific works «Modern structures of metal and wood», 2022)
In the industrial buildings with the support of trussed rafters on the columns at the level of the bottom chord, the main system of horizontal nodes, which the horizontal load rests and provides the rigidity of the building, is located on the bottom chords of trussed rafters. These nodes are usually constructed in the form of trusses (so-called wind trusses). The issue of designing cross trusses with the rational design solutions is relevant. One of the ways to choose the rational design solution for a cross truss is to determine a rational scheme of the web for steel consumption. The method for determining the  web  rational  scheme  of  typical  cross  trusses  on  the  truss  bottom  chords  in  terms  of  material consumption has been developed. This example shows that the cross nodes are 37% more economical than triangular ones with additional posts.